Microwave treatment of oil contaminated drill cuttings produced on offshore oil platforms - Ogunniran, Oluwatosin (2017)
This research project addresses the major processing challenges encountered in the current development of a microwave process, which can treat oil contaminated drill cuttings, from pilot scale to an industrial system. In addition, the dominant mechanism of oil removal during microwave heating of oil contaminated drill cuttings is established for the first time and the implication for the design of an industrial system discussed. Currently, the prevalent practise is to transport oil contaminated drill cuttings produced from drilling activities offshore (United Kingdom Continental Shelf) to land for treatment and disposal. An offshore discharge limit of <1 wt% oil effectively sustains the ship to shore practise, as there are currently no established alternatives that are suitable for offshore operation. A continuous microwave process that can reduce oil levels to <1 wt% has already been developed by researchers to pilot scale with a throughput of 0.5 t/h. This work investigates the two main processing issues encountered during the scaling up and optimisation of the process to an industrial system (4 t/h). They are: 1) thermal runaway and consequent damage to the microwave cavity, 2) effect of the material handling strategy on the efficiency of the microwave process. It was found that the dielectric properties of the clay content of drill cuttings sustained heating rate at temperatures above 100 degree Celsius in drill cuttings. This ensured that the temperature increased from the normal operating temperature of the industrial system (100 degree Celsius) to 400 degree Celsius. The low thermal conductivity of the drill cuttings material is also thought to contribute to the temperature increase from 100 degree Celsius to 400 degree Celsius during processing. At 400 degree Celsius, there is an exponential rise in dielectric constant and loss factor of the drill cuttings material shown to be initiated by the dehydroxylation of the chemically bound water in the clay mineral content. Consequently the temperature of the drill cuttings material increases from 400 degree Celsius to ≥1400 degree Celsius, vitrifying the material and causing thermally induced damages to the microwave cavity. The oil components were found to be transparent to microwaves from ambient temperature to their end point, therefore the exponential rise in dielectric properties at 400 degree Celsius cannot be attributed to the oil content but to the solid phase. Interestingly, the barite and halite mineral components of the drill cuttings material was shown to absorb more microwaves at ≥700 degree Celsius than the clay minerals, suggesting that although thermal runaway is not initiated in the barite and halite components, they ensure vitrification temperatures can be reached. These findings were used to optimise the industrial microwave continuous system by: 1) ensuring no build-up of drill cuttings in the microwave cavity, 2) designing the cavity and process safety systems to ensure temperatures within the cavity does not reach 400 degree Celsius. A twin screw conveyor, which shears the drill cuttings during transport, is the chosen material handling technique within the industrial microwave system. This work demonstrates that the bulk density of drill cuttings can be reduced significantly when sheared. At low microwave power densities, it was found that oil removal from low bulk density materials can be up to 25% less efficient than oil removal from high bulk density materials. However, oil removal efficiency remained the same for both high and low bulk density materials at high power densities. In the past steam stripping, steam distillation and physical entrainment have been identified by researchers as competing mechanism of oil removal from drill cuttings during microwave heating. This work shows that oil removal increases when the steam velocity within the material’s pore increases. It was also shown that high pore steam velocities corresponds to high microwave power densities. Higher oil removals observed at high power densities is as a result of higher pore steam velocities. A mass transfer correlation showing that pore steam velocity has a significant effect on the mass transfer coefficient of oil was developed. The relationship between the pore steam velocity and the mass transfer coefficient shows that steam stripping is the dominant mechanism of oil removal, and accounts for up to 80% oil removal.